RETRACTED: FINANCIAL CONTROL: THEORETICAL APPROACHES - Galina Stankevich; Ekaterina Kasevich (Гуманитарные и юридические исследования)
RETRACTED ARTICLEThe article discusses the main theoretical approaches to the concept of financial control. A comprehensive analysis of this category gives insight into the given institution of financial law in jurisprudence.